Economic progress and policy in developing countries - Maddison, Angus (George Allen and Unwin, 1970)
The book contains a wealth of agricultural an industrial eficiency, fiscal polivy, protectionism, the use of the price mechanism and direct controls; also an examination of the different types of inflation and instability which have plagued developing countries.